10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
In 2017, the European Centre for Disease Prevention and Control developed a public health emergency preparedness logic model for European Union, differentiating between capacities (resources and infrastructure) and response capabilities (actions during emergencies). Analysis of the COVID-19 experience suggests that the main features of this logic model, including the 5 high-level categories of capabilities, remain valid. Some changes are needed, however, in 3 areas. In the detection and assessment area, "laboratory analysis" was integrated with "testing" to better represent their combined role; additionally, "incident recognition," "epidemiological investigation," and "risk characterization" were included under the wider definition of "public health intelligence." In the health services area, "preventive medicine" was replaced with the more specific capability of "coordination of preventive, primary care and other outpatient services (population-based medicine)." In the emergency risk communication area, several capabilities were further clarified such as the use of infodemic management. In addition, the analyses identified 4 overarching issues that must also be consider in preparedness assessments: (1) the need to develop new strategies, approaches, and policies under pressure and to review and revise them as the pandemic evolved; (2) the challenges of implementing an emergency response in the context of a country's internal hierarchical structure of public health, healthcare, and related entities; (3) the need for coordination among the different sections of the healthcare system, particularly hospital and community-based levels; and (4) the challenges of scaling up a country's pandemic response.